Effect of garden cress in reducing blood glucose, improving blood lipids, and reducing oxidative stress in a mouse model of diabetes induced by a high‐fat diet and streptozotocin. (20th January 2020) - Chen, Xi; Yuan, Huaibo; Shi, Fangfang; Zhu, Yudong
Abstract: BACKGROUND: A mouse model in which diabetes mellitus was induced by low‐dose streptozotocin (STZ) injection combined with a high‐fat diet was used to study the effect of two water cress ( Lepidium savitum ) preparations. Diabetic mice were treated with dried cress powder or with water‐soluble extracts (tested at two doses), together with proper control groups. The mice were evaluated after 4 weeks of continuous intervention for type 2 diabetic and associated markers. We determined blood glucose, body weight, total cholesterol (TC), triglyceride (TG), low‐density lipoprotein (LDL), high‐density lipoprotein (HDL), serum insulin levels, and DNA integrity of hepatic cells. The concentrations of malondialdehyde (MDA) and lipid peroxide (LPO) and the activities of four enzymes that are part of the antioxidant defense system were determined in liver samples, as well as gene expression (by semi‐quantitative reverse transcription polymerase chain reaction) and enzyme activity of IRS‐1, IRS‐2, PI3K, AKT‐2, and GLUT4. RESULTS: After 4 weeks of intervention, the levels of TC, TG, and LDL cholesterol were significantly ( P  < 0.5) decreased and HDL cholesterol was significantly increased. Enzyme activities of liver superoxide dismutase, glutathione, glutathione peroxidase, and catalase were significantly increased, whereas MDA and LPO concentrations were significantly reduced. The transcription level of the five genes assessed was increased, with corresponding increases in protein expression. CONCLUSION: Oral uptake of garden cress can significantly reduce the blood glucose and improve the blood lipid metabolism of diabetic mice. Considerable improvements in the activity of antioxidant defense enzymes were observed in type 2 diabetic mice that improved the body's antioxidant emergency response. © 2019 Society of Chemical Industry